The Effect of Seed Collection Time and Color Fruit on the Germination Capacity and Seedling Growth of Mindi (Melia azedarach Linn) - Nurmawati Siregar; Aam Aminah (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2019)
Mindi (Melia azedarach Linn) is versatile type and have good prospects to be developed in plantation programs. One factor that determines the success of the development of this plant is the use of superior quality seeds. Good seeds can be obtained by harvesting physiologically mature fruits. One common indicator often used to determine the maturity of fruit physiologically is the changes of fruit color. The main objective of this research was to determine the effect of seed collection time and fruit color on the germination capacity and seedling growth of mindi. The experimental design used is Factorial Randomized Block Design consist of 2 factors: seed collection time and fruit color. Seed collection time consist of 3 times with 10 days collection time interval. The color fruit differed by 3 colors: green, yellow and brown. Each combination treatment consist of 50 seeds replicated 5 times. Growth responses included germination capacity, survival seedling percentage, seedling length, diameter, root length, dry weight and shoot/root ratio. The result showed that the color fruit significantly affected germination capacity and growth of seedlings. The color of yellow and brown fruit gave the best results for germination’s capacity, while yellow fruits showed high values of percent of seedlings growth, seedling height, dry weight, root length and shoots root ratio. The color of green and yellow fruit gave higher seedling diameter, than the color of brown fruit. The collecting mindi seeds should be done when the fruits are yellow at every collection time.